Dependência e criação de trajetória no terceiro setor: um estudo de caso na Ong Parceiros Voluntários - Oliveira, Talita Raquel de (Universidade do Vale do Rio dos Sinos, 2013)
The purpose of this study was, based on Path Dependence and Path Creation, to identify and analyze the critical events that have occurred and future prospects that influence the strategic choices for the non-governmental organization, Parceiros Voluntários (Voluntary Partners). As main theoretical references regarding Path Dependence, works by Barney (1991; 1995) and other authors of the VBR, such as Teece; Pisano and Shuen (1997), Becker and Ruas (2005), Mahoney (2000) and Balestro et al. (2004), David (2000), Licha (2004), Pierson (2004), Sydow; Schreyogg and Koch (2009) were used. The main references for Path Creation were . Arthur (1989) e Schienstock (2011), Garud and Karnoe (2001), Pham (2007), Henfridsson; Yoo and Svahn (2009) and Garud; Kumaraswamy and Karnoe (2010). The work was done using a case study, semistructured interview with the principal actors of the organization, and Analysis of Content which was done using Nvivo10 software. It was noted that the strategic choices were really influenced by the trajectory of the organization, but there was a variation of intensity in each project and partnership analyzed, since they were not necessarily restricted to what had already been done in the past. In this context, the emerging strategies clearly illustrate this issue, since the organization receives many requests concerning Social Responsibility, and they are all assessed so that innovation is not hindered. It was observed that the organization creates its own methodologies, projects and partnerships, and introduces new elements into the existing structure, confirming that there is complementarity between the constructs of Dependence and Path Creation through critical events such as Project Tribes on the Trails of Citizenship, Project Transparency, the field of “Training”, the help to CSOs (Civil Society Organizations) in the field of management and legislation. And among its future perspectives are extending action to other Brazilian states and other countries, working with Micro and Small Businesses, and an opening for students to do research on the organization.
Keywords: Escolha estratégica; Dependência de trajetória; Criação de trajetória; Terceiro setor; Strategic choice; Path dependence; Path creation; Third sector; ACCNPQ::Ciências Sociais Aplicadas::Administração